[RETRACTED] Identifikasi Gerakan Tanah Longsor Dengan Pendekatan Ground Shear Strain Menggunakan Pengukuran Mikroseismik di Graha Taman Nirwana Kota Semarang - Supriyadi Supriyadi; Rahmad Hafid Hidayatullah; Mahardika Prasetya Aji; Taufik Nur Fitrianto; Rini Kusumawardani (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2020)
This article was retracted due to the following reasons :Article: Identifikasi Gerakan Tanah Longsor dengan Pendekatan Ground Shear Strain Menggunakan Pengukuran Mikroseismik di Graha Taman Nirwana Kota Semarang, Vol. 10 No.1 (2020), pp: 32-36 Author: Supriyadi, R.H, Hidayatullah, Mahardika Prasetya Aji, Taufik Nur Fitrianto, Rini KusumawardaniThis article has been retracted by Publisher with the reason of improper data and error in data processing. All authors of the paper agreed with the reason.